Hubungan Dukungan Sosial Orang Tua dengan Kesulitan Belajar Peserta Didik Kelas XI MIPA di SMA N 1 Padang Sago Kabupaten Padang Pariaman - Nadila Nadila; Joni Adison; Triyono Triyono (Departement of Mathematics Education, 2023)
This study aims to find out (1) a description of parents' social support for children in class XI MIPA at SMAN 1 Padang Sago, Padang Pariaman Regency, (2) a description of students' learning difficulties in class XI MIPA at SMAN 1 Padang Sago, Padang Pariaman Regency, and (3)tested the relationship between parents' social support and students' learning difficulties in class XI MIPA at SMAN 1 Padang Sago, Padang Pariaman Regency. This type of research is a correlational descriptive research. The population in the study were all students in class XI MIPA at SMA Negeri 1 Padang Sago with a total of 78 students. A sample of 32 students was taken using a purposive sampling technique. The instrument used for the study was a closed questionnaire and for correlation analysis using the Correlation Person Product Moment method with the validation results of parents' social support was 0.640 and learning difficulties were 0.545, the results of the reliability of parental social support were Cronbach alpha value 0.963 and learning difficulties were Cronbach alpha value 0. 920. The results showed that: (1) parental social support is in the